Traumatic asphyxia successfully treated with jidabokuippo. Issue 3 (28th September 2020) - Nakae, Hajime; Irie, Yasuhito; Satoh, Kasumi; Kitamura, Toshiharu; Kameyama, Koumei; Furuya, Tomoki; Okuyama, Manabu
ABSTRACT: Case: A 29‐year‐old man presented with traumatic asphyxia associated with symptoms of ecchymosis over the face, conjunctival hyperemia, and a blood‐red puffy face. Jidabokuippo (JDI), a traditional Japanese Kampo medicine to alleviate static blood™ 1 was administered. The blood‐red puffy face improved dramatically. Outcome: Symptoms improved after treatment with JDI. Conclusion: JDI can be used for the management of ecchymosis and swelling following traumatic asphyxia.